Proline Accumulation in Oil Palm Polyembryogenic Cultures Under Various Conditions - Hashim, Ahmad Tarmizi (1992)
Low temperature of 15˚C to 20˚C was observed to suppress the growth and multiplication capacity of oil palm polyembryogenic cultures.This condition enabled the cultures to be maintained for at least six months duration without subculture and thus was suitable for minimal growth storage of invitro cultures. Proline, a .universal stress indicator,was found to accumulate in oil palm cultures under low temperature and moisture stresses(sucrose treatment)but not under anaerobic stress (non-agitated liquid media treatment). Sucrose treatment at 0.5 M caused moisture reduction and induced proline accumulation. In addition, when combined with low temperature storage it extended the low temperature tolerance and prolonged the subculture duration for at least nine months. The application of exogenous proline and ornithine at 10 mM could also induce proline accumulation in the cultures. However, only low level of proline accumulated with application of glutamic acid, glutamine and arginine Inconsistent pattern was observed with pyrroline-S-carboxylic acid (PSC). PSC reductase (EC1.5.1.2) and ornithine aminotrans ferase ( EC2.6.1.13) were found to involve directly/indirectly with proline biosynthes is in polyembryogenic cultures. The specific activities of these enzymes and soluble protein were higher under low temperature and moisture stresses. Since exogenous ornithine could induce proline accumulation and there was an active involvement of ornithine aminotransferase, ornithine could be one of the preferred precursors for proline biosynthes is in oil palm cultures. Similarly, Thioproline (proline analog) increased proline accumulation but produced some toxic effect which eventually killed the cultures. Polyembryogenic cultures were found to utilize the exogenous proline and ornithine more efficiently in the liquid media than in the solid media. The proline in accumulated cultures which were treated with exogenous proline, ornithine and subjected to low temperature stress was observed to return to normal level on transferring to the normal media and conditions. This suggested that the proline accumulated was readily utilizable when re turned to normal condition sand could be considered as a labile metabolite in oil palm polyembryogenic cultures.